Analisis Penerimaan Sistem Presensi Karyawan Berbasis Fingerprint Dengan Metode Technology Acceptence Pada PT. Karex Indo Express - Mulia Rahmayu; Imas Irmalasari (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Absence is attendance data collection which is useful in order to know attendance activity in an institution.PT. Karex Indo Expresss uses employee attendance with fingerprint attendance machines, but not all employees accept the system because they are used to the manual system used before. The purpose of this study was to determine user acceptance of the implementation of the fingerprint presence system. The research uses a quantitative method approach. The model to determine the level of acceptance uses the Technology Acceptance Model (TAM). The results of this study indicate that the order of perception from the most influential is the perception of usefulness, then the perception of convenience, then the perception of the user's attitude, after that the perception of user interest. The conclusion of this study is that the relationship between all perceptions has an influence on the acceptance of this attendance system to support an activity that is almost done every day. Perception of convenience and perception of usefulness are perceptions that trigger in increasing acceptance